Evaluation of generic substitution in Portuguese and Lativan pharmacies - Batista, Rita Isabel Jerónimo (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019